070 What is seronegative neuromyelitis optica spectrum disorder?. Issue 6 (27th May 2022) - Gibbons, Emily; Campgana, Giovanna; O'Connell, Karen; Yeo, Tianrong; Whittam, Daniel; Karthikeayan, Venkatra- man; Leite, Maria Isabel; Palace, Jacqueline; Jacob, Anu; Huda, Saif
Abstract : Background: Most but not all cases of Neuromyelitis Optica Spectrum Disorder (NMOSD) are associated with Aquaporin-4 (AQP4) or myelin oligodendrocyte glycoprotein (MOG) antibodies. Objective: To determine the clinical characteristics of seronegative NMOSD Method: Retrospective review of seronegative NMOSD in Liverpool and Oxford between January 2010–2020 Results: Of NMOSD=727, 49(7%) were seronegative. The male to female ratio was 1:2.5 and median age at onset was 36(5–57) years. In 2/3 of patients the index presentation was myelitis=22 or myelitis+optic neuritis=11. In 26/33 (79%), longitudinally extensive myelitis was present. Optic neuritis=9 (4 bilateral) and brain involvement=7 were also seen. Relapsing disease was observed in 39/49(80%) of patients. The median annualised attack rate was 0.58 over a median disease duration of 78 (3–258) months. Unmatched CSF oligoclonal bands (CSF-OCBs) were detected in 4/38(11%) and 31/49(63%) fulfilled multiple sclerosis (MS) diagnostic criteria. Immunosuppression (typically Mycophenolate and Rituximab) was used in 34/49(69%). Median last EDSS was 4 (1–10) with death recorded in 5/49 (10%) patients. Conclusion: Seronegative NMOSD is uncommon. Longitudinal myelitis with/without optic neuritis is a common initial presentation. Similar to AQP4-IgG, NMOSD disability and mortality rates are high. Absence of unmatched CSF-OCB and typical brain lesions help to distinguish this disease from MS. emily.gibbons@doctors.org.uk